Toward Effective Water Pipe Tobacco Control Policy in the United States: Synthesis of Federal, State, and Local Policy Texts. Issue 4 (July 2017) - Colditz, Jason B.; Ton, Jessica N.; James, A. Everette; Primack, Brian A.
Purpose: Water pipe tobacco smoking (WTS) is growing in popularity among U.S. young adults and is associated with health risks similar to those of cigarette smoking. The purpose of this study is to examine existing tobacco control policies (TCPs) in order to investigate how they engage WTS. Approach: A systematic synthesis of content and legal interactions among federal, state, and local TCP documents. Setting: Pennsylvania, which represents a politically and demographically diverse microcosm of the United States. Participants: No human subjects. Method: Federal and state TCPs were retrieved via public legal repositories. Local policy searches were conducted via county/municipal Web sites, inclusive of 13 localities that had autonomous health departments or existing TCPs based on a National Cancer Institute report. Full-text TCPs were double coded within a grounded theory framework for health policy analysis. Emergent codes were used to compare and contrast policy texts and to examine legal interactions among TCPs. Results: Examination of policy categories including youth access, use restrictions, and taxation revealed WTS as largely omitted from current TCPs. WTS was sometimes addressed as an "other" tobacco product under older TCPs, though ambiguities in language led to questionable enforceability. State preemptions have rolled back or prevented well-tailored reforms at the local level. Federal preemptions have likewise constrained state TCPs. Conclusion: Outdated, preempted, and unclear policies limit the extent to which TCPs engage WTS. Health advocates might target these aspects of TCP reform.